Roles of the Taql and Bsml vitamin D receptor gene polymorphisms in hospital mortality of burn patients - Glaucia R. Nogueira; Paula S. Azevedo; Bertha F. Polegato; Leonardo A.M. Zornoff; Sergio A.R. Paiva; Celia R. Nogueira; Natalia C. Araujo; Bruno H.M. Carmona; Sandro J. Conde; Marcos F. Minicucci (Clinics)
OBJECTIVE: The aim of this study was to evaluate the roles of the Taql and Bsml vitamin D receptor gene polymorphisms in hospital mortality of burn patients. METHODS: In total, 105 consecutive burn injury patients over 18 years in age who were admitted to the Burn Unit of Bauru State Hospital from January to December 2013 were prospectively evaluated. Upon admission, patient demographic information was recorded and a blood sample was taken for biochemical analysis to identify the presence of the Taql(rs731236) and Bsml(rs1544410) polymorphisms. All of the patients were followed over their hospital stay and mortality was recorded. RESULTS: Eighteen of the patients did not sign the informed consent form, and there were technical problems with genotype analysis for 7 of the patients. Thus, 80 patients (mean age, 42.5±16.1 years) were included in the final analysis. In total, 60% of the patients were male, and 16.3% died during the hospital stay. The genotype frequencies for the Taql polymorphism were 51.25% TT, 41.25% TC and 7.50% CC; for the Bsml polymorphism, they were 51.25% GG, 42.50% GA and 6.25% AA. In logistic regression analysis, after adjustments for age, gender and total body surface burn area, there were no associations between the Taql (OR: 1.575; CI95%: 0.148-16.745; p=0.706) or Bsml (OR: 1.309; CI95%: 0.128-13.430; p=0.821) polymorphisms and mortality for the burn patients. CONCLUSIONS: Our results suggest that the Taql and Bsml vitamin D receptor gene polymorphisms are not associated with hospital mortality of burn patients.